The Legal Consequences of Abuse of Power in the Implementation of Development Projects - Aulia, Zuvika Alfi; Samian, Samian; Hardjomuljadi, Sarwono (Universitas Syiah Kuala, 2025)
Legally, the issue of abuse of authority in development is an act that can be prosecuted under two legal frameworks, namely State Administrative Law and Criminal Law. This article analyzes the legal framework and implications of abuse of authority by government officials, with a focus on national strategic projects and the procurement of goods and services. Through normative legal research methods, this study concludes that the Government Administration Law brings a new paradigm by establishing administrative sanctions as the first resort, while criminal sanctions are placed as the last resort. Based on the lex posterior principle, the primary authority to examine the existence of abuse of authority lies with the Administrative Court. Furthermore, the findings prove that officials who unlawfully abuse their authority, causing financial losses to the state, are required to take personal responsibility for the payment of compensation. Although this legal framework aims to provide certainty and prevent the criminalization of policies, its implementation in national strategic projects has drawn criticism for potentially weakening efforts to eradicate corruption. As an implementative measure, this study recommends harmonizing perceptions, developing clear technical guidelines, and improving coordination between APIP, PTUN, and law enforcement agencies. This synergy is expected to ensure the realization of accountability.